2022
DOI: 10.3390/nano12173053
|View full text |Cite
|
Sign up to set email alerts
|

The Release of Non-Extractable Ferulic Acid from Cereal By-Products by Enzyme-Assisted Hydrolysis for Possible Utilization in Green Synthesis of Silver Nanoparticles

Abstract: The present work was undertaken to elucidate the potential contribution of biosynthetically produced ferulic acid (FA) via enzymatic hydrolysis (EH) of rye bran (RB) to the formation of silver nanoparticles (AgNPs) during green synthesis. An analytical approach accomplished by multiple reaction monitoring (MRM) using triple quadrupole mass selective detection (HPLC-ESI-TQ-MS/MS) of the obtained hydrolysate revealed a relative abundance of two isomeric forms of FA, i.e., trans-FA (t-FA) and trans-iso-FA (t-iso-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Recent cutting-edge nanotechnology research has come with the development of plenty of nanoobjects demonstrating multiple functionalities and a range of applicability [13]. In particular, silver nanoparticles (AgNPs) attract tremendous attention from researchers due to their multiple and simultaneous mechanisms of action in combination with antimicrobial agents [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent cutting-edge nanotechnology research has come with the development of plenty of nanoobjects demonstrating multiple functionalities and a range of applicability [13]. In particular, silver nanoparticles (AgNPs) attract tremendous attention from researchers due to their multiple and simultaneous mechanisms of action in combination with antimicrobial agents [14].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have been performed in recent years aimed at the synthesis of AgNPs using a diverse range of plant materials such as Calotropis gigantea [22], Annona Squamosa [23], Acer oblongifolium [24], Cascabela thevetia [25], Cymbopogon citratus [26], Eucalyptus globulus, and Salvia officinalis [27]. However, due to the relative diversity and stability of secondary metabolites, green tea leaves are most frequently reported in the literature as a natural source of reducing agents used in the biosynthesis of AgNPs [13,28]. According to HPLC analysis of the phenolic profile before and after the green synthesis of Ag and gold (Au) NPs using Eucalyptus globulus bark extract, Santos et al [29] revealed that gallic acid and galloyl derivatives were primarily responsible for the reduction of Ag ions to NP.…”
Section: Introductionmentioning
confidence: 99%
“…Later, 100.0 µL of 100 mM AgNO 3 solution was introduced drop-wise, thus providing 1 mM AgNO 3 in the final solution. In this research, NaOH was employed as an accelerator in the green biosynthesis of BL@AgNPs, as reported by Radenkovs et al [39]. Since fructose and fructose-type EPS BL are considered to be non-reducing sugar, their application in the green biosynthesis of AgNPs has not been reported so far.…”
Section: Preparation Of Silver Nanoparticles Using Bacterial Levan Pr...mentioning
confidence: 96%
“…There are currently around 700,000 antibiotic resistance-related deaths each year, and by 2050, this number may increase to 10 million [11,12]. Hence, with the medical benefits of antibiotics decreasing rapidly, researchers have identified nanomaterials as promising alternative antibacterial agents [13]. Nanomaterials and nanoparticles have emerged as innovative antimicrobial materials for treating or preventing infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Extract of Symphyti radix was used in this research as a precursor for silver nanoparticle (AgNP) biosynthesis. AgNPs have been a center of interest for many researchers because of their promising results in terms of their antimicrobial, antifungal, and anti-inflammatory properties [13,34].…”
Section: Introductionmentioning
confidence: 99%